Engineering for Ecosystem Science: Literature Review Utilization of AR Assemblr Edu Media in Elementary Schools - Syafaa Diviella Alayya Violinzky; Ellianawati Ellianawati; Decky Avrilianda (Dinasti International Journal of Education Management And Social Science, 2025)
Education is a lifelong learning experience. Education comes to new challenges to face the era of digitalization. In its development, it requires the latest media, namely Assemblr Edu AR Media. Assemblr Edu is a platform for augmented reality in the form of real 3D in real time that can be downloaded on iOS and Playstore, and its advantages can be used anytime and anywhere. This is one of the IPAS materials related to the reciprocal relationship between biotic and abiotic. The review for this article aims to find out the research trends of Assemblr Edu AR Media on Harmony in Ecosystems. The method used is a systematic literature review with the help of publish or perish related to Assemblr Edu AR Media on Harmony in Ecosystems analyzed from 9 articles indexed by Google Scholar. The results of this study show the results of the AR Assemblr Edu Media research trend on Harmony in Ecosystems which increases significantly every year, the university that conducts a research on AR Assemblr Edu Media on Harmony in Ecosystems the most is the University of Education Indonesia, the learning model used in relevant research is problem-based learning (PBL), The learning model used in relevant research is problem-based learning (PBL), discovery learning model, project-based learning model (PjBL), direct instruction learning model and interactive visualization or called PBL with interactive media, the subject matter is harmony in ecosystems which is dominated by relevant research which is the reciprocal relationship between biotic and abiotic, finally the research on AR Assemblr Edu Media on Harmony in Ecosystems uses a variety of platforms.